2016
DOI: 10.1039/c5cp05864c
|View full text |Cite
|
Sign up to set email alerts
|

Strong room-temperature blue-violet photoluminescence of multiferroic BaMnF4

Abstract: Abstract:BaMnF4 microsheets have been prepared by hydrothermal method. Strong room-temperature blue-violet photoluminescence has been observed (absolute luminescence quantum yield 67%), with two peaks located at 385 nm and 410 nm, respectively. More interestingly, photon self-absorption phenomenon has been observed, leading to unusual abrupt drop of luminescence intensity at wavelength of 400 nm. To understand the underlying mechanism of such emitting, the electronic structure of BaMnF4 has been studied by fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(71 reference statements)
0
5
0
1
Order By: Relevance
“…S2, BaMnF4 powders show the sheet structure, with typical lateral size in the order of 10 μm. Our previous transmission electron microscope (TEM) data confirmed that each BaMnF4 sheet were grown in the ac plane, corresponding to the layered structure [28]. Although the SEM images of other two BaMF4 (M = Co and Ni) (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…S2, BaMnF4 powders show the sheet structure, with typical lateral size in the order of 10 μm. Our previous transmission electron microscope (TEM) data confirmed that each BaMnF4 sheet were grown in the ac plane, corresponding to the layered structure [28]. Although the SEM images of other two BaMF4 (M = Co and Ni) (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…BaMF4 (M = Mn, Co, Ni) powders were synthesized using hydrothermal method, and finally resulted in pale pink, rose red, and golden yellow powders for M = Mn, Co, and Ni, respectively [28][29][30]. To prepare the electrodes, the electroactive materials BaMF4 were mixed with acetylene black and polyvinylidene fluoride (PVDF) with a mass ratio of 8:1:1, and then fully milled with N-methyl-2-pyrrolidone (NMP).…”
Section: Fabrication Of Bamf4 and Electrodesmentioning
confidence: 99%
“…9,10 The mixture of BaF 2 and Ni(CH 3 COO) 2 ·4H 2 O with stoichiometric ratio were dissolved in trifluoroacetic acid solution (volume ratio 1:1 for CF 3 COOH and distilled water), enclosed into 23 mL autoclave, heated to 220 • C and held for 20 hours, then slowly cooled down to room temperature. The obtained precipitates were cleaned by ethanol and distilled water, and dried in vacuum oven at 95 • C for 6 hours, resulting in the final yellow powder.…”
Section: Methodsmentioning
confidence: 99%
“…However, the AFM ordering usually emerges at a much lower temperature, typically T N < 50 K. It should be mentioned that multiferroic fluorides have been less addressed as compared with other type-I multiferroics, perhaps due to the difficulties in synthesis of high-quality materials and electric characterization. In addition, strong room-temperature blue–violet photoluminescence in BaMnF 4 was found very recently [ 42 ], a surprising functionality in multiferroic fluorides.…”
Section: Type-i Multiferroicsmentioning
confidence: 98%